Liquid–liquid phase separation and conformational strains of α-Synuclein: implications for Parkinson’s disease pathogenesis - Ruiz-Ortega, Eva D.; Wilkaniec, Anna; Adamczyk, Agata (Frontiers in Molecular Neuroscience, 2024)
Parkinson’s disease (PD) and other synucleinopathies are characterized by the aggregation and deposition of alpha-synuclein (α-syn) in brain cells, forming insoluble inclusions such as Lewy bodies (LBs) and Lewy neurites (LNs). The aggregation of α-syn is a complex process involving the structural conversion from its native random coil to well-defined secondary structures rich in β-sheets, forming amyloid-like fibrils. Evidence suggests that intermediate species of α-syn aggregates formed during this conversion are responsible for cell death. However, the molecular events involved in α-syn aggregation and its relationship with disease onset and progression remain not fully elucidated. Additionally, the clinical and pathological heterogeneity observed in various synucleinopathies has been highlighted. Liquid–liquid phase separation (LLPS) and condensate formation have been proposed as alternative mechanisms that could underpin α-syn pathology and contribute to the heterogeneity seen in synucleinopathies. This review focuses on the role of the cellular environment in α-syn conformational rearrangement, which may lead to pathology and the existence of different α-syn conformational strains with varying toxicity patterns. The discussion will include cellular stress, abnormal LLPS formation, and the potential role of LLPS in α-syn pathology.